2018
DOI: 10.1007/s40291-018-0323-2
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Event Simulation Model to Assess the Economic Value of a Hypothetical Pharmacogenomics Test for Statin-Induced Myopathy in Patients Initiating a Statin in Secondary Cardiovascular Prevention

Abstract: We found that a strategy favoring patients staying on statin therapy is cost effective even if patients maintained on statin are at risk of rhabdomyolysis. Our results are explained by the fact that statins are highly effective in reducing the CV risk in patients at high CV risk, and this benefit largely outweighs the risk of rhabdomyolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…E 2 is secreted by the follicles in the ovaries, and this hormone can promote increased endometrial thickness and provide conditions for conception [ 21 ]. LH, SH, and E 2 levels are too low, then the sinus follicles are recruited and selected, inhibiting the formation of dominant follicles and leading to the occurrence of anovulation [ 22 ]. The combination of letrozole with urotropin significantly increases reproductive hormone levels and facilitates the production of estrogen in the late follicular development and postovulatory luteal phase, which acts on the endometrium and increases its thickness, making it more conducive to pregnancy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…E 2 is secreted by the follicles in the ovaries, and this hormone can promote increased endometrial thickness and provide conditions for conception [ 21 ]. LH, SH, and E 2 levels are too low, then the sinus follicles are recruited and selected, inhibiting the formation of dominant follicles and leading to the occurrence of anovulation [ 22 ]. The combination of letrozole with urotropin significantly increases reproductive hormone levels and facilitates the production of estrogen in the late follicular development and postovulatory luteal phase, which acts on the endometrium and increases its thickness, making it more conducive to pregnancy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the use of a pharmacogenomic test is a beneficial strategy for any test costing less than CAN$356 (Canadian dollars) [35]. This was further supported by another study that found that in highrisk populations, using pharmacogenomic testing is also cost-effective to maintain patients on a statin given the cardiovascular benefit, despite possible risk of rhabdomyolysis [36].…”
Section: The Somatosensory Amplification Scale (Sas)mentioning
confidence: 57%
“…Other approaches such as using decision trees might be limited by the robustness of findings as it over-simplifies the complexity of the consequences of the decisions [ 20 ]. While the Discrete Event Simulation (DES) model is more flexible and offers retention of patient history and risk profile updates for each event, it is much more complicated and not readily replicable compared to the Markov model [ 19 , 21 ]. Decision models such as the decision tree are too simplistic, while the dynamic model requires advanced knowledge in statistics or programming and usually more preferable in infectious disease modelling [ 13 ].…”
Section: Discussionmentioning
confidence: 99%